Higher education in a changing world: proceedings of the HERDSA Conference 2005, 3-6 July 2005 Sydney, Australia - HERDSA Conference (2005 : Sydney); Brew, Angela; Asmar, Christine; Higher Education Research and Development Society of Australasia (Australia : Higher Education Research & Development Society of Australasia Inc., 2005)
This 2005 conference offer opportunities to engage critically and creatively with new ideas and research about teaching and learning and higher education more generally
Keywords: Education, Higher -- Congresses; Education, higher -- Developing countries -- Congresses